ANALYSIS OF SOIL MACROFAUNA DIVERSITY IN DRAGON FRUIT AREA AT AL-ASRI FRUIT GARDEN APPLIED WITH PALM OIL MILL EFFLUENT - Mardhatillah, Siti; Hanel John, Arlen; Sartina Siregar, Etti (Universitas Medan Area, 2025)
The presence and diversity of soil macrofauna in dragon fruit areas that are not applied with Palm Oil Mill Effluent (POME) and those applied with POME as fertilizer, with variations in application time, can reflect different soil qualities. This study aims to analyze species presence, Diversity Index (H') soil macrofauna, and its correlationwith application POME in dragon fruit areas without application (Block I) and those applied with POME (Pond 5) PT. Anugrah Tanjung Medan, with variations in waste application time 14 days (Block II) and 28 days (Block III). The research used Purposive Sampling method, and soil macrofauna sampling with Quadrat and Hand Sorting methods. The results of the study revealed 52 species of soil macrofauna, with 28 species Block I, 40 species Block II, and 37 species Block III. The highest H' value for soil macrofauna was found in Block II (3.08), categorized as high diversity, followed by Block III (2.87) and Block I (2.72), which were categorized as moderate diversity. These results indicate that utilization of POME as fertilizer for 14 days (Block II) has a positive correlation with increase in the presence and diversity of soil macrofauna, contributing to improved soil quality.